Optimal fiscal and monetary policy in a medium-scale macroeconomic model - Stephanie Schmitt-Grohé; Martín Uribe (European Central Bank (ECB), 2006)
In this paper, we study Ramsey-optimal fiscal and monetary policy in a mediumscale model of the U.S. business cycle. The model features a rich array of real and nominal rigidities that have been identified in the recent empirical literature as salient in explaining observed aggregate fluctuations. The main result of the paper is that price stability appears to be a central goal of optimal monetary policy. The optimal rate of inflation under an income tax regime is half a percent per year with a volatility of 1.1 percent. This result is surprising given that the model features a number of frictions that in isolation would call for a volatile rate of inflation—particularly nonstate-contingent nominal public debt, no lump-sum taxes, and sticky wages. Under an income-tax regime, the optimal income tax rate is quite stable, with a mean of 30 percent and a standard deviation of 1.1 percent.
Keywords: E52; E61; E63; 330; Inflation Stabilization; Nominal and Real Rigidities; Ramsey Policy; tax smoothing; Time to Tax; Konjunkturtheorie; Finanzpolitik; Geldpolitik; Optimale Besteuerung; Theorie; USA